Expressivism, Relativism, and the Analytic Equivalence Test - Frápolli, Maria J.; Villanueva, Neftalí (Frontiers in Psychology, 2015)
The purpose of this paper is to show that, pace (Field 2009, 252), MacFarlane’s assessment relativism and expressivism should be sharply distinguished. We do so by arguing that relativism and expressivism exemplify two very different approaches to context-dependence. Relativism, on the one hand, shares with other contemporary approaches a bottom-up, building block, model, while expressivism is part of a different tradition, one that might include Lewis’ epistemic contextualism and Frege’s content individuation, with which it shares an organic model to deal with context-dependence. The building-block model and the organic model, and thus relativism and expressivism, are set apart with the aid of a particular test: only the building-block model is compatible with the idea that there might be analytically equivalent, and yet different, propositions.